2015
DOI: 10.1089/thy.2014.0362
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Testing of Thyroid Fine-Needle Aspirations Improves Presurgical Diagnosis and Supports the Histologic Identification of Minimally Invasive Follicular Thyroid Carcinomas

Abstract: Molecular testing of air-dried FNA samples improves presurgical diagnosis. Discrepant sensitivities and specificities reported previously are most likely related to the use of different grading schemes resulting in different compositions of the cytologic categories, interobserver variability to diagnose follicular variant of papillary thyroid carcinomas and a different prevalence of RAS mutations in follicular carcinomas. The knowledge of the molecular testing might support the histologic identification of min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 26 publications
8
66
4
Order By: Relevance
“…Actually, several authors have demonstrated the feasibility of molecular testing (including NGS) in routine thyroid FNA using air-dried, spray-fixed, ethanol-fixed smears, or even liquid-based cytology (LBC) material preserved in alcoholic fixative solution (33,34,35).…”
Section: Molecular Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, several authors have demonstrated the feasibility of molecular testing (including NGS) in routine thyroid FNA using air-dried, spray-fixed, ethanol-fixed smears, or even liquid-based cytology (LBC) material preserved in alcoholic fixative solution (33,34,35).…”
Section: Molecular Testingmentioning
confidence: 99%
“…From these data, a malignancy risk stratification of patients with an AUS/FLUS and FN/SFN diagnosis can be evaluated to decide whether or not surgery is indicated (36). The gain in sensitivity attributable to the application of molecular tests to FNA material is around 20%, reaching 80% as opposed to 60% with cytological analysis alone (35). We should be aware that the main disadvantage of the application of molecular mutational tests to thyroid FNA remains the fact that 30-40% of thyroid cancers do not harbor known mutations.…”
Section: Molecular Testingmentioning
confidence: 99%
“…Formalin fixation leads to the crosslinking of nucleic acids and proteins, fragmentation of isolated nucleic acid material, and the possibility of sequence alterations. This point needs to be considered when other sources of samples such as cell block or cytology preparation with preserving liquid are used and specific protocols have to be applied in order to obtain high-quality nucleic acid isolation [16] Different types of specimen obtained from thyroid FNA procedure may be used for molecular analysis: (a) cells collected from FNA during the procedure [11], (b) cells retrieved from FNA-stained smears [1], (c) cells retrieved from air-dried slides [17], and (d) paraffin sections from cell blocks. All these samples have been shown to be suitable for point mutation analysis as well as for detecting chromosome rearrangements [17].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Nucleic acid recovering from direct smears offers relevant advantages: first, it permits to check the cells before nucleic acid isolation, allowing the analysis of exactly those cells that are cytologically indeterminate and the enrichment of the pathological population [16, 17]. This is not possible if a dedicated pass of FNA is washed in a tube containing nucleic acid preservative solution.…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 1 more Smart Citation